2021
DOI: 10.4236/ae.2021.94014
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Lymphatic Filariasis Co-Transmission in Endemic Health Districts in Burkina Faso

Abstract: Introduction: Lymphatic filariasis (LF) and malaria are two vector-borne diseases which parasites can simultaneously infect human or mosquito. In Burkina Faso, studies mainly focused on the control of these diseases independently. Hence, there is a lack of information on their co-transmission of to both human and vector. The present study aimed at providing baseline data from endemic areas in Burkina Faso towards a successful integrated management of both diseases. Methods: The study was carried out in six sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A recent study has showed that An. nili was W. bancrofti potential vector [27] in this region. Other Anopheles species in particular An.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has showed that An. nili was W. bancrofti potential vector [27] in this region. Other Anopheles species in particular An.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the meta-analysis showed that the pooled prevalence of malaria and filariasis co-infections among participants was 11% (95% confidence interval (CI): 8%-13%, I 2 , 96.7%, 17 studies; Fig 3). The highest prevalence was demonstrated by the study conducted in Tanzania (14%, 95% CI: 11.4%-17.1%) [33], whereas the lowest prevalence was demonstrated by studies conducted in India (0.1%, 95% CI: 0%-0.2%) [22] and in Burkina Faso (0.1%, 95% CI: 0%-0.4%) [27].…”
Section: Prevalence Of Malaria and Filariasis Co-infections Among Sel...mentioning
confidence: 99%
“…We estimated the pooled prevalence of malaria and filariasis co-infections among participants using the data available from 17 studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Results of the meta-analysis showed that the pooled prevalence of malaria and filariasis co-infections among participants was 11% (95% confidence interval (CI): 8%-13%, I 2 , 96.7%, 17 studies; Fig 3).…”
Section: Prevalence Of Malaria and Filariasis Co-infections Among Sel...mentioning
confidence: 99%
See 2 more Smart Citations